2022
DOI: 10.3389/fsoc.2022.958108
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic policies and breastfeeding: A cross-sectional study during the onset of COVID-19 in the United States

Abstract: The United States is one of the few countries, and the only high-income country, that does not federally mandate protection of postpartum employment through paid postpartum maternity and family leave policies. At the onset of the COVID-19 pandemic in the U.S., stay-at-home orders were implemented nationally, creating a natural experiment in which to document the effects of de facto paid leave on infant feeding practices in the first postpartum year. The purpose of this cross-sectional, mixed-methods study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…Another study also found that participants in the United Kingdom who had stopped BF were more likely to have been told by health professionals or friends and family that BF was unsafe or to have been told that having symptoms of COVID‐19 did not allow BF (Costantini et al, 2021 ). Similar findings were reported during the first wave of the COVID‐19 pandemic in the United States (Palmquist et al, 2022 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another study also found that participants in the United Kingdom who had stopped BF were more likely to have been told by health professionals or friends and family that BF was unsafe or to have been told that having symptoms of COVID‐19 did not allow BF (Costantini et al, 2021 ). Similar findings were reported during the first wave of the COVID‐19 pandemic in the United States (Palmquist et al, 2022 ).…”
Section: Discussionsupporting
confidence: 86%
“…For example, one mother stated, 'I was employed but we went to online sessions, and I had planned to resign so as to breastfeed, but Mothers desired to receive more in-person support from peers, family, childcare providers and lactation specialists during their lactation periods (Snyder & Worlton, 2021). A larger mixedmethods study conducted during this same period for the United States found that 66% of participants who were BF before the COVID-19 stay-at-home orders continued BF and of these 31% breastfed for longer than they had initially planned due to increased close proximity to their infants (Palmquist et al, 2022). Perceptions of the importance of BF and human milk in providing immunological protection to their infants were a key factor to continue BF despite the circulation of conflicting guidance from HCW.…”
Section: Themementioning
confidence: 99%
“…Our nding does not align with studies reporting a decrease in breastfeeding rates and support during the pandemic (6, 8). However, these ndings align with the literature reporting that COVID-19 stay-at-home orders delay breastfeeding cessation plans (32).…”
Section: Discussionsupporting
confidence: 88%
“…While our analysis highlights that the challenges to breastfeeding existed across all the six pillars, these were complex and systemic. It is inadequately understood as to how populations and health systems respond to public health emergencies given their unique lived experiences, risk perceptions and preparedness ( 61 ). Nevertheless, breastfeeding practices continue to be amenable to socio-cultural influences, at least in resource constrained settings ( 62 – 64 ).…”
Section: Discussionmentioning
confidence: 99%